Eksplorasi Model Penilaian Kinerja Guru Pendidikan Agama Islam di Sekolah Menengah Atas di Jawa Barat - Moh. Syarif Hidayat; Muharir; Sartono; Hisam Ahyani; Muhammad Safdar Bhatti (Jurnal Pendidikan Indonesia, 2026)
Teacher performance assessment that has been implemented so far often focuses primarily on administrative or technical aspects, and therefore does not fully reflect the actual quality of the learning process. This study aims to explore the implementation and the need for developing a performance assessment model for Islamic Religious Education (PAI) teachers at the senior high school level. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews, field observations, and document analysis. Informants were selected purposively, consisting of PAI teachers, school principals, and PAI supervisors. The data were analyzed using the interactive analysis model proposed by Miles and Huberman. The findings reveal that the existing teacher performance assessment model remains largely administrative in nature and does not adequately incorporate aspects such as personality, spirituality, and the exemplary character expected of PAI teachers. These findings indicate the need to develop a more holistic and contextual assessment model to measure teachers’ contributions to character formation and the internalization of Islamic values among students. Teacher performance evaluation for PAI teachers should therefore be oriented not only toward technical competencies but also toward moral integrity and the transformative role of teachers in education. A structured and contextual performance assessment model enables schools to provide more accurate and relevant feedback for the development of pedagogical, professional, social, and personal competencies of PAI teachers.